Celebrity Endorser Terhadap Keputusan Pembelian Produk Somethinc melalui Brand Image pada Marketplace Shopee (Studi pada Mahasiswi Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura) - Wahdania, Nova Cahya; Chrismardani, Yustina (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research discusses problems with Somehinc products. The purpose of this research is to explain the influence of Celebrity Endorsers on purchasing decisions for Somethinc Products, to explain the influence of Celebrity Endorsers on the Brand Image of Somethinc Products, to explain the influence of Brand Image on Purchase Decisions for Somethinc Products, to determine the influence of Celebrity Endorsers on purchasing decisions for Somethinc Products through Brand Image Somethinc Products. This research uses a quantitative approach using the path analysis method, with a total of 123 respondents. The results of this research are (1) Celebrity Endorser has a significant influence on purchasing decisions (2) Celebrity Endorser has a significant influence on Brand Image (3) Brand Image has a significant influence on Purchase Decisions (4) Celebrity Endorsers have a significant influence on purchasing decisions through Brand Image.